Short term improvement in exercise capacity and symptoms following exercise training in interstitial lung disease. Issue 6 (1st February 2008) - Holland, A E; Hill, C J; Conron, M; Munro, P; McDonald, C F
Abstract : Background: Interstitial lung disease (ILD) is characterised by exertional dyspnoea, exercise limitation and reduced quality of life. The role of exercise training in this diverse patient group is unclear. The aims of this study were to establish the safety of exercise training in ILD; its effects on exercise capacity, dyspnoea and quality of life; and whether patients with idiopathic pulmonary fibrosis (IPF) had similar responses to those with other types of ILD. Methods: 57 subjects with ILD (34 IPF) were randomised to receive 8 weeks of supervised exercise training or weekly telephone support. The 6 min walk distance (6MWD), incremental exercise test, modified Medical Research Council (MRC) dyspnoea score and Chronic Respiratory Disease Questionnaire (CRDQ) were performed at baseline, following intervention and at 6 months. Results: 80% of subjects completed the exercise programme and no adverse events were recorded. The 6MWD increased following training (mean difference to control 35 m, 95% CI 6 to 64 m). A significant reduction in MRC score was observed (0.7 points, 95% CI 0.1 to 1.3) along with improvements in dyspnoea (p = 0.04) and fatigue (p<0.01) on the CRDQ. There was no change in peak oxygen uptake; however, exercise training reduced heart rate at maximum isoworkload (p = 0.01). There were no significant differences in response between those with and without IPF. After 6 months there were no differences between the training and control group for any outcome variable. Conclusions: Exercise training improves exercise capacity and symptoms in patients with ILD, but these benefits are not sustained 6 months following intervention. Trial registration number: NCT00168285